The Evolving Practice of Marriage Contracts in Islamic Family Law: Customary Influences and Legal Implications - Tamamiyah, Lutfiyatut (Journal of Islamic Family Law, 2025)
Islamic family law is a foundational framework for marriage contracts, which is influenced by local customs. This study aims to explore how these customary influences shape the practice of marriage contracts and examine the legal implications of such variations, focusing on the balance between religious adherence and cultural adaptation. The study employs a qualitative approach to analyze the evolving practice of Islamic marriage contracts across diverse cultural contexts, identifying trends and challenges in balancing religious guidelines with local traditions. The results suggest that Islamic family laws, when flexible, can accommodate diverse cultural landscapes while maintaining the essence of religious guidelines. Additionally, the study suggests developing guidelines that balance respect for cultural traditions with adherence to core Islamic principles. The research highlights the importance of a balanced approach that respects cultural traditions while ensuring that Islamic principles of justice and fairness are upheld. This research provides valuable insights for legal scholars, policymakers, and religious authorities who are navigating the challenges of aligning traditional Islamic values with contemporary legal standards.